(untitled) (Религиски дијалог и соработка, 2025)
The scientific paper before us will question the role, scope and importance of Orthodox Christianity in social issues, especially in the case of the Serbian Orthodox Church (SPC). The topic of the scientific work is focused on questioning the connections between the specifically Orthodox experience of religion and its place in contemporary (Serbian) society. Therefore, the views of church dignitaries of the Serbian Orthodox Church regarding the role of the Orthodox faith in social issues were selected as the subject of research. Through his research, the author has set himself the goal of predicting the possibilities of establishing and building the social teaching of the Serbian Orthodox Church. The increasingly active role of religious communities and churches in contemporary society: from culture, through politics and economy to the natural environment points to the legitimate social significance of the basic assumptions of this scientific paper. The questioning of theoretical assumptions, religious conceptions and spiritual-political phenomena: fundamentalism, integralism and secularism on the example of an isolated case study in the ideas and value positions of dignitaries and theologians of the Serbian Orthodox Church leads to an indisputable innovative contribution and scientific justification of the research. After all, the SOC has always been the foundation of the national rallying of the Serbian ethnos, and the main lever of national identity, so the overall justification of the topic is greater. In the paper, the author started from the initial assumption that the current opinion in the Serbian Orthodox Church is not favorable towards the establishment of the social teaching of the Serbian Orthodox Church. The research was based on numerous methods in social sciences, such as: observation, case study, content analysis, comparative approach...